PENDEKATAN SETS (SCIENCE, ENVIRONMENT TECHNOLOGY AND SOCIETY) DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI MATERI SISTEM EKSKRESI PADA MANUSIA KELAS XI MIPA-3 DI SMA NEGERI 1 KEMBANG TANJONG - Eli Nurhayati (Jurnal Sains Riset, 2022)
This study aims to determine the application of the SETS approach (Science, Environment, Technology, and Society) in improving student learning outcomes in class XI MIPA-3 SMA Negeri 1 Kembang Tanjong. This research is a Classroom Action Research (CAR) on students of class XI MIPA-3 SMA Negeri 1 Kembang Tanjong. In this study, the researcher used one class to apply the SETS (Science, Environment, Technology, and Society) approach, namely class XI MIPA-3 SMA Negeri 1 Kembang Tanjong which consisted of 25 students, consisting of two cycles, each cycle includes steps planning, implementing actions, observing and reflecting. At the planning stage, learning scenarios are prepared and learning tools are prepared. In the implementation of the action, the learning process is carried out with the SETS approach. The results of the observations are presented in class discussions. At the observation stage, observations were made of student activities, student attitudes, and teacher performance. As well as learning outcomes tests. Performance indicators in the research are the achievement of individual and classical learning mastery.The results of the implementation of the first cycle showed that the indicators of success had not been achieved because the learning outcomes of students only reached 72% or 18 with an average value of 75.2 students who had completed learning, for this reason, improvements were made again in cycle II. The analysis in the second cycle shows the completeness of student learning outcomes with an average value of 94.2 and 24 students or 96% of students complete learning. Thus, the application of the SETS (Science, Environment, Technology, and Society) approach in improving student learning outcomes for class XI MIPA-3 SMA Negeri 1 Kembang Tanjong has been successful.Keywords: SETS approach, learning outcomes